2016
DOI: 10.1016/j.ijsu.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Log odds of positive lymph nodes is a superior prognostic indicator in stage III rectal cancer patients: A retrospective analysis of 17,632 patients in the SEER database

Abstract: The prognostic value of LNR can be confounded by LODDS. In stage III rectal cancer patients, LODDS has superior discrimination power over LNR and can more accurately evaluate CSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…As a novel nodal assessment approach, LODDS has been proposed because of the limitation of the N descriptor and LNR in the prediction of prognosis. Also, it has been identified to be superior to N descriptor and LNR in many cancers including esophageal carcinoma 16‐21 . However, the prognostic accuracy of LODDS for patients with esophageal carcinoma who received neoadjuvant therapy remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a novel nodal assessment approach, LODDS has been proposed because of the limitation of the N descriptor and LNR in the prediction of prognosis. Also, it has been identified to be superior to N descriptor and LNR in many cancers including esophageal carcinoma 16‐21 . However, the prognostic accuracy of LODDS for patients with esophageal carcinoma who received neoadjuvant therapy remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that in some tumors such as rectal and gastric cancers, LNR lost its prognostic efficacy in survival prediction for patients without metastatic lymph nodes retrieved 8,15 . Recently, the log odds of positive lymph nodes (LODDS), defined as the natural logarithm of the ratio of a metastatic lymph node to a nonmetastatic lymph node, 16 were found to be effective in prediction of survival outcomes for rectum, gastric, pancreatic, breast, and esophageal cancers 16‐21 . To date, the value of LODDS in the prediction of survival outcomes for patients with esophageal carcinoma who received neoadjuvant therapy has never been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently suggested the limitation of traditional LNM status in prognosis stratification of stage III patients, strongly urging us to investigate whether the Fn level has the capacity to provide an accurate stratification for these patients. 39 , 40 We therefore subsequently performed a subgroup analysis and found that Fn level could stratify the CSS and DFS of both stage IIIB and IIIC patients, but failed in stage IIIA patients. This result suggested that Fn level might be an effective prognostic indicator only for stage IIIB or IIIC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Persiani et al used Cox regression to demonstrate the same relationship with the LODDS results, but not with those from LNR, in a series of 258 patients with non-metastatic colon cancer [ 24 ]. In a study including 17,632 cases, Huang et al demonstrated that the LODDS method was more accurate than the LNR when calculating specific survival rates [ 25 ]. On the other hand, other authors have demonstrated that both methods are directly related to survival [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%